Biospecific labeling with undecagold: visualization of the biotin-binding site on avidin - Safer, D; Hainfeld, J; Wall, J S; Reardon, J E (Science (American Association for the Advancement of Science), 1982)
The biotin-binding site on avidin has been labeled with biotin conjugated to undecagold, an organometallic cluster compound containing 11 gold atoms in a core angestroms in diameter. Examination of unstained specimens by scanning transmission electron microscopy reveals the labeled sites directly, without computational averaging or filtering of the images. This approach should be widely applicable for determining the locations of subunits and functional site in biological macromolecules at a resolution at a resolution in range of 15 angstroms.